2014
DOI: 10.1371/journal.pone.0110908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraosseous Erythropoietin during Hemorrhagic Shock in Swine

Abstract: ObjectiveTo determine whether erythropoietin given during hemorrhagic shock (HS) ameliorates organ injury while improving resuscitation and survival.MethodsThree series of 24 pigs each were studied. In an initial series, 50% of the blood volume (BV) was removed in 30 minutes and normal saline (threefold the blood removed) started at minute 90 infusing each third in 30, 60, and 150 minutes with shed blood reinfused at minute 330 (HS-50BV). In a second series, the same HS-50BV protocol was used but removing an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…As discussed above, the addition of vasopressin infusion in an series from a previous study markedly improved initial resuscitation and subsequent 72 hour survival relative to a preceding series in which only fluid resuscitation with normal saline was used before blood reinfusion for the same hemorrhagic shock severity [ 9 ]. For the present study, pigs were randomized 2:1 to vasopressin or no vasopressin.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As discussed above, the addition of vasopressin infusion in an series from a previous study markedly improved initial resuscitation and subsequent 72 hour survival relative to a preceding series in which only fluid resuscitation with normal saline was used before blood reinfusion for the same hemorrhagic shock severity [ 9 ]. For the present study, pigs were randomized 2:1 to vasopressin or no vasopressin.…”
Section: Methodsmentioning
confidence: 99%
“…The preceding study [ 9 ] also showed that in the presence of vasopressin initial resuscitability and 72 hour survival could be achieved successfully administering a reduced amount of normal saline (corresponding to half the amount of blood withdrawn) or no fluids at all. Thus, for the present series we also examined whether normal saline could be required.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Erythropoietin (EPO), a well-known hormone for red blood cell proliferation, has been reported to protect organs and tissues against ischemia-reperfusion injuries. Recently, it is administered in low-flow states such as HS and has shown beneficial effects in this condition (Borovnik-Lesjak et al 2014). Therefore, erythropoietin was added into the resuscitative fluid to evaluate its protective effects on organs following HS.…”
Section: Introductionmentioning
confidence: 99%